Sequential or parallel decomposed processing of two-digit numbers? Evidence from eye-tracking. - Moeller, Korbinian; Fischer, Martin H.; Nuerk, Hans-Christoph; Willmes, Klaus (Quarterly Journal of Experimental Psychology, 2009)
A study investigated the effectiveness of sequential and parallel decomposition models in predicting the fixation pattern in a two-digit number magnitude comparison task. These models were tested by examining participants' eye fixation behavior while choosing the larger of two numbers. The stimulus set was composed of within-decade and between-decade comparisons, with the latter further split into compatible and incompatible trials and trials with different decade and unit distances. The observed fixation pattern suggested that the comparison of two-digit numbers were not performed by sequentially comparing decade and unit digits as proposed by Poltrock and Schwartz but rather in a decomposed but parallel manner. In addition, the fixation data provided first evidence that digit processing in multi-digit numbers is not an unadulterated bottom-up effect but is also affected by top-down factors. Implications for multi-digit number processing are discussed.